Помогите, пожалуйста, упростить выражение, подробно. Спасибо. [latex]( \sqrt{8+2 \sqrt{7} } + \sqrt{8-2 \sqrt{7} } )^{2} [/latex]

Помогите, пожалуйста, упростить выражение, подробно. Спасибо. [latex]( \sqrt{8+2 \sqrt{7} } + \sqrt{8-2 \sqrt{7} } )^{2} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
=(√(8+2√7) )²+2√(8+2√7)*√(8-2√7) +(√(8-2√7) )²= =8+2√7+2√(8+2√7)(8-2√7) +8-2√7=16+2√(8²-(2√7)²=16+2√(64-4*7)=16+2√(64-28)=16+2√36=16+2*6=16+12=28
Гость
(√(√7+1)²+√(√7-1)²)²=(√7+1+√7-1)²=(2√7)²=4*7=28
Не нашли ответ?
Ответить на вопрос
Похожие вопросы